KOMUNIKASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: (Studi pada PT. Solo Murni Kiky Creative Product Di Surakarta) - Ronny Isnaryanto (JURNAL WIDYA GANECWARA, 2020)
This study aims to determine the effect of motivation, communication and work discipline on employee performance (study at PT. Solo Murni Kiky Creative Products in Surakarta). The population in this studywwere 100 employees. The data used in this research is secondary data. The method in sampling uses non random sampling technique. From the sampling technique to produce a sample of 20. This typ of quantitative and analytical research techniques used multiple linear regression using SPSS version 16. Multiple linear regression analysis using the classic assumption test include normality test, multicollonity test, heteroscedasticity test, and autocorrelation test. To test the variables used the coefficient of determination test, t-test, f-test. The results of the study simultaneously showed that the variables of communication, motivation, and discipline had a significant effect on work performance. The results of the partial communication test have no effect on employee performance. Motivation and work discipline have an effect and significant effect on employee performance.